Understanding the effects of supervisory and coworker safety communication on construction workers' behavior - Lyu, Sainan; Xi, Jiade; Cui, Peng; Zhang, Rita Peihua; Jiang, Xiaoyan; Zhang, Beibei (Frontiers in Public Health, 2025)
On high-risk construction sites, frontline workers are constantly exposed to dual channels of safety communication: supervisory safety communication (SSC) and coworker safety communication (CSC). While existing research has emphasized the general importance of safety communication in promoting safety performance, the differentiated effects and psychological mechanisms of SSC and CSC remain underexplored. To address this gap, this study aims to adopt a Conservation of Resources (COR) theory framework to examine how SSC and CSC influence construction workers' safety behavior (SB) through psychological mechanisms, and how these effects vary under different levels of work pressure (WP). A survey was conducted with 359 frontline construction workers in large-scale projects across China, and data were analyzed by multiple linear regression and an interaction analysis with simple slopes. Results show that SSC (β = 0.234, p < 0.001) and CSC (β = 0.545, p < 0.001) both positively affect SB. Mediation analysis confirmed the roles of SKSE, SM, and POS, with SM showing the strongest effect (β = 0.235, p < 0.001). WP was found to weaken SSC's effects but not CSC's. These findings advance COR theory by clarifying psychological resource pathways in safety communication. Practically, the study suggests differentiated strategies for leveraging supervisory and coworker communication to enhance safety under varying work pressures.